METHANE CONVERSION OVER Mo/Al2O3 – CATALYSTS MODIFIED WITH ADDITIVES OF ZEOLITE AND PHOSPHOROUS - Nurmakanov Y.Y.; Zakumbayeva G.D.; Itkulova S.S.; Komasko L.V. (Academic Scientific Journal of Chemistry, 2019)
Mo-containing catalysts supported on a matrix consisting of alumina modified with additives of both zeolite – HZSM and phosphorus were synthesized. The molybdenum content was varied within a range of 1-5 mas.%. The physicochemical properties of the catalysts were studied by BET, XRD, electron microscopy, and microdiffraction analysis. The catalytic properties of the synthesized catalysts were tested in the processes of dry and combined steam-dry conversion of methane. It was shown that the synthesized catalysts are the nanosystems with particle sizes are 3-50 nm depending on the amount of molybdenum and the processing methods of the catalysts. The activity of the catalysts grows with increasing of both molybdenum content and temperature. The main product of methane conversion is synthesis gas. The Н2/СО ratio increases at adding steam to an initial feed. In dry reforming of methane the reaction products also contain C2, C6 hydrocarbons and alcohols.